2014
DOI: 10.1093/pcp/pcu036
|View full text |Cite
|
Sign up to set email alerts
|

tassel-less1 Encodes a Boron Channel Protein Required for Inflorescence Development in Maize

Abstract: tassel-less1 (tls1) is a classical maize (Zea mays) inflorescence mutant. Homozygous mutant plants have no tassels or very small tassels, and ear development is also impaired. Using a positional cloning approach, ZmNIP3;1 (a NOD26-like intrinsic protein) was identified as the candidate gene for tls1. The ZmNIP3;1 gene is completely deleted in the tls1 mutant genome. Two Mutator-insertional TUSC alleles of ZmNIP3;1 exhibited tls1-like phenotypes, and allelism tests confirmed that the tls1 gene encodes ZmNIP3;1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…An additional allele identified from the RescueMu population had a Mu insertion in the 59 untranslated region ( Figure 5B). Attempts to amplify any part of the tls1 coding region (AGPv2 (Leonard et al, 2014). In summary, the identification of eight tls1 alleles with mutations in the maize NIP3;1 confirms that tls1 encodes the major intrinsic protein NIP3;1.…”
Section: Positional Cloning Of Tls1mentioning
confidence: 80%
See 3 more Smart Citations
“…An additional allele identified from the RescueMu population had a Mu insertion in the 59 untranslated region ( Figure 5B). Attempts to amplify any part of the tls1 coding region (AGPv2 (Leonard et al, 2014). In summary, the identification of eight tls1 alleles with mutations in the maize NIP3;1 confirms that tls1 encodes the major intrinsic protein NIP3;1.…”
Section: Positional Cloning Of Tls1mentioning
confidence: 80%
“…Bayesian phylogenetic analysis of maize tls1 and similar NIPs from other plant species revealed that tls1 falls in a well-supported (>0.95 posterior probability) monocot-specific clade along with rice NIP3;1a ( Figure 6) (Hanaoka et al, 2014;Leonard et al, 2014). This grass tls1 clade is sister to another well-supported grass clade containing four rice sequences, three sorghum (Sorghum bicolor) sequences, and the maize NIP471 sequence.…”
Section: Positional Cloning Of Tls1mentioning
confidence: 94%
See 2 more Smart Citations
“…In Arabidopsis, NIP5;1 and BOR1 are polarly localized at the distal and proximal side of the plasma membrane of the root cells, respectively (Takano et al, 2010), and their cooperative transport is required for efficient and directional uptake of B in the roots especially under a B-limited condition Reid 2014). Homologs of Arabidopsis NIP5;1 and BOR1 have been functionally characterized in other plant species such as rice (Oryza sativa), barley (Hordeum vulgare), rapeseed (Brassica napus), and maize (Zea mays; Nakagawa et al, 2007;Sutton et al, 2007;Chatterjee et al, 2014;Durbak et al, 2014;Hanaoka et al, 2014;Leonard et al, 2014;Zhang et al, 2017). Basically, they have a similar role in B uptake, although the expression patterns differ somewhat within plant species.…”
mentioning
confidence: 99%